A computational study of fractional model of atmospheric dynamics of carbon dioxide gas. (January 2021) - Dubey, Ved Prakash; Dubey, Sarvesh; Kumar, Devendra; Singh, Jagdev
Abstract: In this paper, a fractional order nonlinear mathematical model describing the dynamics of atmospheric concentration of CO2 is investigated and studied through the application of a semi-analytical homotopy scheme combined with Sumudu transform and homotopy polynomials. This study examines the consequences of the variations of forest biomass and human population on the dynamics of the concentration of CO2 gas in the atmosphere. The Caputo fractional derivatives are engaged in this study. The computational work shows that the evaluated iterative terms are adequate for the refined approximations of the solutions for a fractional model of dynamics of atmospheric concentration of CO2, and thus authenticate the computational strength of the employed scheme. The variational behavior of concentration of CO2, forest biomass, and human population are demonstrated through the graphical presentation regarding the changing values of fractional order derivatives and time t . Moreover, this study also examines the analysis of obtained solutions for a fractional model in view of uniqueness and convergence.